Les shoppings malls de Rabat : des espaces publics « par défaut » pour les jeunes adolescents Rbatis - Tarik Harroud (Enfances, Familles, Générations, 2018)
Research Framework: Due to their offer and their spatial configuration, shopping malls in Morocco attract heterogeneous crowds, including the young people and the teenagers who make practices there remember the public places of the city Objectives : The contribution studies the social practices and the images which associate the young people and particularly the teenagers with the commercial spaces as new places of meeting and sociability Methodology : The work combines interviews realized with around thirty young people and teenagers and observations concerning their social practices made in some malls of Rabat Results : The contribution shows how this malls is the object of images and strong representations which these young and teenagers associated previously with the public places of the capital. They set up themselves, for them, as of new public places where the image, by, the virtual, the hedonism and the consumerism occupy a dominating place in their relationship to the urbanity Conclusions : She shows that dimensions such as the safety, the animation, the consumption and the simulation are more and more preponderant elements in the report of the young people and the teenagers in the public places, justifying their appreciation in malls with regard to the traditional public places. Contribution : Malls must be thought than what of the private, closed and trade places but more and more the supports of a new urbanity highlighting new reports in the city and in the public place.